Unraveling the Therapeutic Enigma of Liposomes in Ocular Drug Delivery - Sandip Karmakar; Sreejan Manna; Tamal Jana; Sougata Jana; Gouranga Nandi (Journal of Bio-X Research)
The ocular delivery of drugs has always presented a pharmaceutical challenge. Various ocular barriers, such as reflex blinking, tear turnover, epithelial tight junctions, metabolism in ocular tissues, efflux pumps, nasolacrimal drainage, and other blood ocular barriers, restrict corneal permeation to ocular therapeutic moieties. This has limited the ocular bioavailability for many drugs. The short residence time of the drug on the ocular surface area also limits bioavailability. The small size and attractive surface properties of liposomal formulations offer advantages in ocular drug permeation. Accordingly, liposome-based preparations have attracted increasing attention from pharmaceutical researchers for delivering drugs on the ocular surface. Recent research has supported the potential of liposomal carriers for the successful delivery of various drugs, including antiglaucoma, anti-inflammatory, anti-infection, and anti-hypertensive drugs. The various ocular barriers are discussed here in detail, and the synthesis regimes of several liposomal drug carriers are described along with their applications in delivering different therapeutic agents to the ocular region. This review concisely describes the current status and future prospects of liposomal drug delivery systems for ocular drug delivery.